217 THE USE OF SIILO MESSAGING APP BETWEEN HOSPITAL-BASED FRAILTY INTERVENTION THERAPY TEAM AND COMMUNITY-BASED EMERGENCY DEPARTMENT IN THE HOME TEAM. (25th October 2022) - Davis, AJ; O'Grady, S; Donohoe, N; Hill, R; Langton, S; Delaney, A; Doyle, C; Sweeney, A; Van Den Berg, N; Nally, SM
Abstract: Background: Effective communication is an important component of any healthcare system. There is frequent communication of patient care and information between the EDITH (Emergency Department In The Home) and the FIT (Frailty Intervention Therapy) teams, which are based across two sites. Traditionally handovers between therapists were completed via email/ fax. Siilo is a secure medical messaging app designed to facilitate instant communication of patient information between healthcare professionals in a confidential manner. Methods: A 3-month pilot of the Siilo app was commenced in August 2021 to improve the flow of information between teams, facilitate timely decision making and improve patient care. A questionnaire to rate speed, efficiency, accuracy, accessibility and confidentiality on a 4point scale was completed by all therapy staff members. Qualitative questions regarding positive and negative aspects, and future suggestions were included. Results: Pre-pilot the median time from EDITH assessment to receipt of handover was 20 hours. During the pilot, median time to handover was 1 hour. Speed, efficiency and accessibility of communication between teams received a median rating of 2 ("average") pre-pilot, increasing to 4 ("excellent") during the pilot. Accuracy and confidentiality received a median rating of 3 ("good") pre-pilot, improving to a median rating of 4 ("excellent"). 100% of respondents reported Siilo had a positive impact on decision making and on patient care.Qualitative themes included; earlier acute care discharge planning; ease of use and reduction in paperwork. Suggestions to further improve communication between the services were made and will be explored at a later date. Conclusion: A significant reduction in time from assessment to handover improved the flow of communication between the teams, reduced duplication of assessments and improved patient care for older patients. Confidentiality and accuracy were maintained over this period. The use of the app will be continued and suggestions to further improve the integration between the services will be implemented.